Sustainable management of wastewater use in agriculture: a systematic analysis - Ghanbari, Mina; Naeimi, Amir; Bijani, Masoud (Frontiers in Sustainable Food Systems, 2024)
Due to changes that have occurred in ecological conditions, the requirement to use wastewater has been considered more seriously in the agricultural sector, because agriculture is the source of human nutrition, health and security. Based on this, the purpose of this research was to systematically analysis the components affecting sustainable management of wastewater use (SMWWU) in the viewpoint of critical theory paradigm. Inductive qualitative content analysis (IQCA) was used for systematic analysis. In this regard, the software used was MAXQDA. The statistical population included valid scientific articles and knowledgeable experts in wastewater management in the agricultural sector in Tehran province, Iran. The sampling method for articles was by searching based on keywords and for experts by purposeful method until theoretical saturation was reached. The results of IQCA in the form of a model showed that the six main components “economic,” “environmental,” “contextual,” “individual,” “management and planning” and “education and extension” affect SMWWU. Each of these components also includes several factors and variables that can strengthen SMWWU and reduce the water crisis by paying attention to them. The obtained model can be used by policy makers and interested parties in making decisions and planning water protection measures.